Friendly fire : the accidental shootdown of U.S. Black Hawks over Northern Iraq - Snook, Scott A., 1958- (Princeton University Press, 2000)
"On April 14, 1994, two U.S. Air Force F-15 fighters accidentally shot down two U.S. Army Black Hawk Helicopters over Northern Iraq, killing all twenty-six peacekeepers onboard. This book attempts to make sense of this tragedy - a tragedy that on its surface makes no sense at all." "With almost twenty years in uniform and a Ph. D. in organizational behavior, Lieutenant Colonel Snook writes from a unique perspective. A victim of friendly fire himself, he develops individual, group, organizational, and cross-level accounts of the accident and applies a rigorous analysis based on behavioral science theory to account for critical links in the causal chain of events. By explaining separate pieces of the puzzle, and analyzing each at a different level, the author removes much of the mystery surrounding the shootdown. Based on a grounded theory analysis, Snook offers a dynamic, cross-level mechanism he calls "practical drift"--The slow, steady uncoupling of practice from written procedure - to complete his explanation."--Jacket.